Peningkatan Kesejahteraan Masyarakat melalui Pengembangan UMKM Cilok sebagai Penguatan Moderasi Beragama di Desa Kalicinta - Okta Firnando; M. Iskandar; Siti Zumrotus Saadah (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) is an essential strategy to improve the welfare of rural communities. Kalicinta Village has local potential in the form of the traditional food cilok, which can be developed into a productive and competitive business. This community engagement aims to analyze the role of cilok MSMEs in enhancing community welfare, identify challenges, and formulate strengthening strategies based on local potential. The method employed was Participatory Action Research (PAR), involving the community actively in problem identification, action planning, implementation, and evaluation. Data were collected through observation, interviews, and focus group discussions. The results show that cilok MSMEs contribute to increasing household income, absorbing local labor, and empowering women, while also strengthening social cohesion through values of togetherness. The main challenges include limited capital, market access, digital literacy, and managerial capacity. Interventions such as training, product innovation, digital marketing, and government support effectively enhance competitiveness. Through a participatory approach, cilok MSMEs have the potential to become a pillar of the village economy and a sustainable model of local empowerment.